Integrated in silico identification of cholinesterase inhibitors from Nyctanthes arbor-tristis - Qazi Mohammad Sajid Jamal; Ali H. Alharbi; Varish Ahmad; Khurshid Ahmad (PLoS ONE, 2025)
Alzheimer’s disease (AD) remains a major neurodegenerative disorder, characterized by cognitive decline alongside functional impairments that affect daily living. Natural therapeutic alternatives have spurred the search for novel inhibitors targeting acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), two well-established targets in AD therapy. This study utilizes an in silico methodology to investigate new cholinesterase inhibitors sourced from Nyctanthes arbor-tristis, a plant known for its abundant bioactive phytochemicals. Through virtual screening, molecular dynamics simulations (MDS), free energy landscape analysis, and ADMET predictions, eight compounds have been identified as potential inhibitors of AChE and/or BChE. These compounds include Apigenin, Arborside-B, Arbortristoside-D, Arbortristoside-E, Nicotiflorin, Arborside-A, Beta-amyrin, and Nyctanthic acid. These compounds exhibited robust binding affinities compared to the control, advantageous ADMET profiles, and sustained stability throughout 200 ns of MDS and energy assessments, highlighting their potential as viable drug candidates for further exploration. Further experimental studies are required to validate their therapeutic efficacies, thereby confirming their potential as neurological therapeutics for the treatment of AD and related disabilities.